Scylla queen of the strait - Brace, Salvatore; Diving World Production ([S.l.] : Diving World Production, 1998)
Extraordinary tales of Greek mythology and legend have accompanied Scylla through the ages. Evocative scenes from the past bring the Strait and the town of Scylla to life underlining the uniqyeness of its people with the reportage of the ancient and moving sword fish hunting ritual
VCD format
Keywords: Crab fisheries; Crabs